Goodbye Christopher Robin A. A. Milne and the making of Winnie-the-Pooh - Thwaite, Ann 1932-; Cottrell Boyce, Frank 1959- (St. Martin's Griffin, 2017)
"Goodbye Christopher Robin: A.A. Milne and the Making of Winnie-the-Pooh is drawn from Ann Thwaite's Whitbread Award-winning biography of A. A. Milne , one of England's most successful writers. After serving in the First World War, Milne wrote a number of well-received plays, but his greatest triumph came when he created Winnie-the-Pooh, Piglet, Tigger, Eeyore and, of course, Christopher Robin, the adventurous little boy based on his own son. Goodbye Christopher Robin inspired the film directed by Simon Curtis and starring Domhnall Gleeson, Margot Robbie and Kelly Macdonald. It offers the reader a glimpse into the relationship between Milne and the real-life Christopher Robin, whose toys inspired the magical world of the Hundred Acre Wood. Goodbye Christopher Robin is a story of celebrity, a story of both the joys and pains of success and, ultimately, the story of how one man created a series of enchanting tales that brought hope and comfort to an England ravaged by the First World War"...